Becoming a non-immigration country with immigrants: the institutional regime of Japanese immigration policy towards economic migrants - Komine, A (2014)
How can one detect and understand change in the face of apparent continuity? This is the question which has been asked by some scholars of institutionalism. One way of answering this is to make analytical room for incremental change as an endogenous source of institutional transformation. Put bluntly, one does not always need spectacular exogenous events, such as wars and revolutions, to explain institutional change. The present thesis is a qualitative case study of Japan’s immigration policy towards economic migrants since the 1980s. Its aim is to uncover a causal mechanism behind the policy development by drawing on a model of institutional change put forward by James Mahoney, Wolfgang Streeck and Kathleen Thelen. At first, the inquiry may seem ill-founded for Japan is neither an immigration country nor an immigrant-receiving country. Indeed, the country still lacks an immigration policy to speak of, and immigrants continue to be called gaikokujin (foreigners) as opposed to imin (immigrants). A closer examination of the recent policy development, however, shows that the content and practice of Japanese immigration policy simply belie its self-description. Since 2012 the Japanese government has admitted highly-skilled migrants as potential permanent residents using a points-based system and has incorporated foreigners into the resident register system for Japanese citizens in order to facilitate their integration into Japanese society. The central claim of the present research is that Japanese immigration policy has become increasingly settlement-oriented as an unexpected consequence of earlier policy decisions and that the change has been endogenously effected without dismantling the pre-existing institution of immigration management. In making this claim, I particularly draw attention to the way in which a cumulative effect of minor changes eventually transformed the basic nature of the policy institution.